Iranian EFL students' perception of willingness to communicate in an extramural digital context - Soyoof, Ali (Interactive learning environments, 2023)
This study explored factors that have influenced Iranian English as a Foreign Language (EFL) learners' willingness to communicate (WTC) in an extramural digital (ED) context, an ever-increasing second language (L2) communication context. To this end, the researcher interviewed 50 Iranian secondary school language learners. Having used thematic analysis, four broad sources influencing students' L2 WTC were found, such as educational practices (K-12 instruction), interpersonal variables (familiarity with the interlocutors and supportive communities), affective variables (L2 confidence and anxiety in ED context), and social variable (intergroup climate). More importantly, these factors seem to influence each other during communication in the ED contexts. This study can broaden our understanding of how Iranian secondary students use ED contexts to improve their L2 WTC. Understanding these factors can give insight to Iranian policymakers and teachers to promote the L2 WTC of Iranian students in classroom contexts.